Potential changes on anammox activity after Chicxulub asteroid impact - Pérez Díaz, Noel; Martín González, Osmel; Cárdenas Ortiz, Rolando Pedro (Springer, 2019)
The activity of anammox bacteria (AA) can be estimated based on the production of N2. Known the mechanism of the catabolic reaction, three differential equations are established according to the most important substrates (NO 3 and NHþ 4 ) and the pH. The solution of this system might provide a rough estimate of the activity of the anammox, since neither inhibitory effects nor efficiency of the microorganisms is considered. Anammox can be inhibited by ocean acidification, generated by the deposition of H2SO4 and HNO3 during asteroid impact events such as Chicxulub. The magnitude of the inhibition depends on the amount and speed with which the H2SO4 is added fundamentally.
Keywords: Anammox Activity; Ocean Acidification; Asteroid Impact; Earth and Planetary Astrophysics; Atmospheric and Oceanic Physics; Geophysics